Bridging the Gap: Analyzing Volunteerism Barriers to the International Humanitarian NGOs in Egypt - Fouad, Heba (AUC Knowledge Fountain, 2025)
In Egypt, volunteerism, within international humanitarian non-governmental organizations (NGOs), functions in distinctive characteristics influenced by, among other things, cultural, educational, and economic factors. NGOs face challenges and obstacles in attracting motivated volunteers, engaging and training volunteers, as well as managing the staff-volunteers relationship, and implementing adequate human resources (HR) policies and strategies. In this context, this thesis seeks to bridge the knowledge gap of volunteerism challenges in Egypt, delving deep into understanding the barriers existing within the international humanitarian NGOs that directly and indirectly influence its volunteer engagement levels. The thesis also aims to understand the successful implementation of policies and procedures that encourage and facilitate effective volunteering engagement. In order to fulfill these objectives, semi-structured interviews were conducted with volunteers and employees of the Egyptian Red Crescent, the Catholic Relief Services, and the Cares Egypt international humanitarian NGOs. The findings of the study indicate that while the Egyptian ecosystem and NGOs' policies and procedures may affect individuals in diverse ways, a professional volunteer management approach that addresses factors such as volunteers' motivational aspects, effective relationships with direct supervisors, and proper recognition for the workload and volunteers’ availability can directly and positively impact volunteering engagement when implemented effectively. Therefore, it is essential to advocate for a professional volunteer management approach that ensures effective volunteer selection and onboarding, effective implementation of supervision techniques and volunteer feedback and communication, implementation of a volunteer recognition program that emphasizes high performance, identification of volunteers' strengths and interests to provide opportunities for skill development and ensuring volunteer flexibility and work-life balance. Ultimately, the implementation of such management policies and strategies can provide volunteers with a pleasant experience while ensuring the effective operation of NGOs, leading to constant and effective volunteer engagement.